2018
DOI: 10.3892/mmr.2018.9533
|View full text |Cite
|
Sign up to set email alerts
|

NF‑κB inhibitor DHMEQ inhibits titanium dioxide nanoparticle‑induced interleukin‑1β production: Inhibition of the PM2.5‑induced inflammation model

Abstract: PM2.5 is a particle with a diameter <2.5 µm that is often involved in air pollution. Nanoparticles <100 nm are thought to invade the trachea and lungs to cause inflammation, possibly through the activation of macrophages. On the other hand, titanium dioxide (TiO 2) particles can be used in models of nano-micro-sized particles, as one can prepare the particles with such sizes. TiO 2 particles are classified into Rutile, Anatase, and Brookite types by their crystal structure. Among them, Anatase-type TiO 2 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Mature IL‐1β and IL‐18 are then released to extracellular space 7 . Interestingly, as an effector of the NLRP3 inflammasome, IL‐1β is a pluripotent pro‐inflammatory cytokine involved in the process of PM2.5‐induced respiratory diseases and considered to play a pivotal role in pulmonary inflammation pathogenesis 8 . For example, Xu et al showed that PM2.5 exposure induced IL‐1β signaling activation and resulted in pulmonary inflammation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Mature IL‐1β and IL‐18 are then released to extracellular space 7 . Interestingly, as an effector of the NLRP3 inflammasome, IL‐1β is a pluripotent pro‐inflammatory cytokine involved in the process of PM2.5‐induced respiratory diseases and considered to play a pivotal role in pulmonary inflammation pathogenesis 8 . For example, Xu et al showed that PM2.5 exposure induced IL‐1β signaling activation and resulted in pulmonary inflammation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The NF‐ĸB inhibitor structurally related to the antibiotic epoxyquinomycin was reported to inhibit the nuclear translocation of NF‐κB RelA (p65) in TNFα‐stimulated cells without information on the nuclear transport of other SRTFs . This inhibitor also reduced the expression of IL‐1β in human THP‐1 cells challenged with titanium dioxide particles and also reduced skin inflammation in a murine model of atopic dermatitis . Ivermectin, a broad‐spectrum antiparasitic compound, was identified as an inhibitor of importin α/β nuclear import involved in the nuclear transport of some viral proteins .…”
Section: Other Nuclear Import Inhibitorsmentioning
confidence: 99%
“…184 This inhibitor also reduced the expression of IL-1β in human THP-1 cells challenged with titanium dioxide particles and also reduced skin inflammation in a murine model of atopic dermatitis. 185,186 Ivermectin, a broad-spectrum antiparasitic compound, was identified as an inhibitor of importin α/β nuclear import involved in the nuclear transport of some viral proteins. 187 Its selectivity towards individual importins α remains unclear.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Pro-inflammatory stimuli LPS and IFNγ act via TLR4 to trigger STAT1 phosphorylation and up-regulate the expression of STAT1-dependent genes, and its effect is prolonged by MONPs [125,126]. In the THP1 monocytic cell line, an NFκB inhibitor attenuated Il1β production induced by TiO2 NPs [66]. The anti-inflammatory potential of NPs is also controlled via NFκB down-regulation [57].…”
Section: Functional Outcome Of Nanoparticle-macrophage Interactionsmentioning
confidence: 99%